2000
DOI: 10.1038/sj.bjp.0703120
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of small‐conductance Ca2+‐activated K+ channels stably expressed in HEK 293 cells

Abstract: 1 Three genes encode the small-conductance Ca 2+ -activated K + channels (SK channels). We have stably expressed hSK1 and rSK2 in HEK 293 cells and addressed the pharmacology of these subtypes using whole-cell patch clamp recordings. 2 The bee venom peptide apamin blocked hSK1 as well as rSK2 with IC 50 values of 3.3 nM and 83 pM, respectively. 3 The pharmacological separation between the subtypes was even more prominent when applying the scorpion peptide blocker scyllatoxin, which blocked hSK1 with an IC 50 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 34 publications
(50 reference statements)
5
147
2
Order By: Relevance
“…5C). A similar inward rectification was also observed for rSK2 expression in HEK 293 cells (37). A few minutes after break-in to the whole cell configuration, the hSK2 current has the tendency to hSK2 with rSK2, aSK2, hSK3, rSK3, hSK1, and rSK1.…”
Section: Human Leukemic Jurkat T Cells Express Apamin-and Dtc-mentioning
confidence: 51%
See 1 more Smart Citation
“…5C). A similar inward rectification was also observed for rSK2 expression in HEK 293 cells (37). A few minutes after break-in to the whole cell configuration, the hSK2 current has the tendency to hSK2 with rSK2, aSK2, hSK3, rSK3, hSK1, and rSK1.…”
Section: Human Leukemic Jurkat T Cells Express Apamin-and Dtc-mentioning
confidence: 51%
“…Recent studies revealed that Ca 2ϩ gating involves the constitutive association of calmodulin with a C-terminal domain of SK channel ␣ subunits (31)(32)(33)(34). Some cloned isoforms of SK channels are blocked by apamin and by d-tubocurarine (dTC), a plant alkaloid (29,(35)(36)(37). The residues Asp 341 and Asn 368 on either side of the deep pore of the ␣ subunit were shown to be the primary determinants of apamin and dTC sensitivity (35 In this study, we cloned from human Jurkat T cells a 2.5-kb full-length cDNA, hSK2, encoding the human isoform of SK2 channels.…”
Section: Camentioning
confidence: 99%
“…This, along with the lower apamin sensitivity of homomeric SK channels, may seem to support the hypothesis that SK1 underlies the apamin-insensitive sAHP. However, this idea seems still difficult to reconcile with the observation that the hippocampal sAHP seems to be entirely resistant to high concentrations of apamin, which completely block the homomultimeric SK1 channels tested in different expression systems (Shah and Haylett, 2000a;Strobaek et al, 2000;Grunnet et al, 2001b). This hypothesis might, however, be rescued if there exist auxiliary (␤) subunits that substantially alter the toxin sensitivity of the SK channel complex, such as the BK-␤4 subunits have been found to do for BK channels (Meera et al, 2000).…”
Section: Discussionmentioning
confidence: 71%
“…It was therefore suggested that the sAHP is mediated by SK1 channels. However, the findings that the sAHP is resistant to apamin (up to 1 M; Lancaster and Nicoll, 1987;Storm, 1989;Stocker et al, 1999), whereas SK1 homomeric channels are blocked by this toxin (Shah and Haylett, 2000a;Strobaek et al, 2000;Grunnet et al, 2001a), have, together with other pharmacological and kinetic discrepancies, cast doubt on the proposed causal relationship between SK1 and the sAHP (Shah and Haylett, 2000b;Shah et al, 2001;Faber and Sah, 2002). Meanwhile, a complex alternative splicing pattern of mouse and rat SK1 genes have been discovered (Shmukler et al, 2001), with some splice variants lacking the calmodulin-binding domain.…”
mentioning
confidence: 99%
“…As previously described (Strøbaek et al, 2000), K i values were calculated based on current versus time plots and the kinetics of drug-induced reduction in the current. This is fitted with the nonequilibrium version of the Michaelis-Menten equation:…”
Section: In Vitromentioning
confidence: 99%